PENGARUH PENAMBAHAN SARI JAMBU BIJI MERAH TERHADAP KADAR TOTAL VITAMIN C, AKTIVITAS ANTIOKSIDAN DAN SIFAT ORGANOLEPTIK ES KRIM TOMAT - Atikah Ammar Hanif (2021)
The accumulation of excess fat increases inflammation that develops metabolic complications. Guava contains high vitamin C as an antioxidant to fight pro inflammation. The purpose of this study was to analyze the effect of adding guava juice on total vitamin C levels, antioxidants and organoleptic properties of tomato ice cream, determine the formula, determine the nutritional content and physical properties (melting power and overrun) of the selected formula. The research design used a one-factor completely randomized design. The factors consisted of 3 tomato ice cream formulas with different proportions of adding red guava juice, including F1 (43.4%), F2 (46.5%), and F3 (49.6%). Organoleptic data analysis used Kruskall Wallis, while total vitamin C levels and antioxidant activity used the ANOVA test with further tests if the effect of the treatment was found. The statistical test showed no effect on the addition of red guava juice on vitamin C levels (p> 0.05) and antioxidant activity (p> 0.05) but it did affect the panelists' preference for each parameter (p <0.05), among others color, aroma, texture and taste. Determination of the selected formula using the Exponential Comparison Method. The selected formula was F3 (49.6%) with moisture content 90.5%, ash content 0.3%, protein 0.98%, fat content 1.14%, carbohydrate content. 6.95%, levels of vitamin C 37.5 mg / 100gr, antioxidant activity 6028.0 ppm, melting rate 18 minutes / 10 gr and overrun 36.7%.